Ocular TGF-β, Matrix Metalloproteinases, and TIMP-1 Increase with the Development and Progression of Diabetic Retinopathy in Type 2 Diabetes Mellitus. (28th June 2021) - Saucedo, Lucia; Pfister, Isabel B.; Zandi, Souska; Gerhardt, Christin; Garweg, Justus G.
Abstract : Diabetic retinopathy (DR) is a sight-threatening late complication of diabetes mellitus (DM). Even though its pathophysiology has not been fully elucidated, several studies suggested a role for transforming growth factor- (TGF-) β, matrix metalloproteinases (MMPs), and tissue inhibitors of matrix metalloproteinase (TIMP) in the onset and progression of the disease. Consequently, the aim of this study was to analyze the concentrations of TGF- β 1, TGF- β 2, TGF- β 3, MMP-3, MMP-9, and TIMP-1 in patients with different stages of DR in order to identify stage-specific changes in their concentrations during the progression of the disease. Serum and aqueous humor (AH) samples were collected during intraocular surgery, and eyes were classified into the following groups: healthy controls (n = 17 ), diabetic patients with non-apparent DR (n = 23 ), mild/moderate nonproliferative DR (NPDR) (n = 13 ), and advanced NPDR/proliferative DR (PDR) without vitreal hemorrhage (n = 14 ). None of the patients had been under anti-VEGF or laser treatment within six months prior to surgery. In the AH, TGF- β 1 levels increased in advanced NPDR/PDR by a factor of 5.5 compared to the control group. Similarly, an increase in MMP-3 and TIMP-1 levels in the AH was evident in the later stages of DR, corresponding to a 7.7- and 2.4-fold increase compared to the control group, respectively, whereas serum levels of the studied proteins remained similar. In conclusion, increased concentrations of TGF- β 1, MMP-3, and TIMP-1 in the AH, but not in the serum, in advanced NPDR/PDR indicate that the intraocular regulation for these cytokines is independent of the systemic one and suggest their involvement in the progression of DR.